The Double-Fortified Salt (Iodized Salt with Iron) Consultation: A Process for Developing Evidence-Based Considerations for Countries. Issue 1 (15th February 2021) - Houston, Robin; Tsang, Becky L; Gorstein, Jonathan
ABSTRACT: The addition of iodine to edible salt has been one of the most important public health successes of the past half century, enabling most countries to achieve optimal iodine intake and protect the brains of unborn children from the adverse consequences of iodine deficiency. Salt has been an ideal vehicle for this effort because of its near universal and narrow range of consumption, relative ease of technology for salt iodization, and capacity for virtually all salt producers to add iodine. As a result of the success of salt iodization, there has been growing interest in using salt as a vehicle for other important micronutrients, particularly the addition of iron to iodized salt to produce double-fortified salt (DFS), to combat the persistent problem of iron deficiency and iron deficiency anemia. Because of this growing interest in DFS and the need for a comprehensive review of evidence to support the viability of this intervention, the Iodine Global Network (IGN) initiated a global consultation to gather all available data on different aspects of DFS. IGN identified 4 key areas considered essential to understand for a successful fortification intervention: 1 ) efficacy and effectiveness, or how well DFS produces a health impact in controlled and real-life settings; 2 ) technical considerations for production, or what are the minimum requirements to manufacture DFS; 3 ) program implementation to describe experiences thus far with the delivery of DFS across multiple platforms; and 4 ) comparison of DFS with other iron fortification efforts to determine the comparative advantage of DFS to improve iron intake and prevent iron deficiency anemia. This preface provides an overview of the DFS Consultation objectives, process, and objectives.